Adat Pernikahan Melayu Jambi Perspektif ‘Urf dalam Ilmu Ushul Fiqh - Muhammad Sibawaihi; Mokhammad Baharun (Program Pascasarjana Universitas Ibrahimy, 2017)
Marriage has rules and regulations its implementation. According to Jambi Malay customary law, there are several stages in marriage custom, especially in subdistrict of Muara Tembesi, first introduction period, second preparation period. thirth day scales, fourth betel tanyo Pinang tanyo, fifth tand fill custom lumbago, sixth take delivery customs lumbago, seventh marriages marry, eight old gather, memulang lek pado penangga, ninth Berelek Berkenduri, complain Gather tuo. Next custom marriage is absolutely must be followed by all society of jambi because of the moral sanction if someone doesn’t follow applicable law. The purpose of research is to know the custom marriage of Jambi Malay and position of custom law, especially in subdistrict of Tembesi. research method is Islamic law research, research type used is field research. The research approach used is a normative approach, the problems studied under Islamic law, to underestand the Qur'an, Hadith, and 'Urf in Ushul Fiqh. The research method used is observation, interview, and documentation. Data analysis used is qualitative analysis. Based on the research has done, it can be concluded the marriage custom of Jambi Malay in Muara Tembesi Subdistrict, the analysis of `Urf is shohih custom.